Protective Effects of Dietary Vitamin D3, Turmeric Powder, and Their Combination against Gasoline Intoxication in Rats - Gulfira A. Yestemirova; Zura B. Yessimsiitova; Michael Danilenko (MDPI AG, 2024)
The inhalation of gasoline vapors (GV) is associated with developing various pathologies. Particularly, oil refinery and gas station workers are at a greater risk of developing lung cancer, kidney cancer, bladder cancer, and hematological disorders, including acute myeloid leukemia. Therefore, preventing the harmful effects of GV and alleviating their consequences appear to be important and timely issues. In this study, we investigated the potential of vitamin D3, turmeric powder, and their combination to ameliorate the toxicity of gasoline fumes in rats. Separate groups of animals fed with a standard rodent diet, with or without the supplementation of vitamin D3 (750 IU/kg body weight) and/or turmeric powder (0.5%, w/w, in food), were untreated or treated with GV (11.5 ± 1.3 cm3/h/m3/day) for 30, 60, or 90 days. Changes in the body weight were monitored weekly. Histological, biochemical, and hematological parameters were determined at the end of each treatment period. While the exposure of rats to GV resulted in a time-dependent reduction in body weight, supplementation with vitamin D3, but not with turmeric root powder or their combination, partially prevented weight loss. Macroscopical and histological analyses showed pronounced time-dependent changes in the organs and tissues of GV-treated rats. These included alveolar wall collapse in the lungs, the destruction of the lobular structure and hepatocytolysis in the liver, the shrinkage and fragmentation of glomeruli in the kidneys, and the disorganization of the lymphoid follicles in the spleen. However, co-treatment with the nutritional supplements tested, especially vitamin D3, noticeably alleviated the above conditions. This was accompanied by a significant improvement in the blood chemistry and hematological parameters. Collectively, our results demonstrate that the harmful effects of environmental exposure to GV can be reduced upon supplementation of vitamin D3. The fact that the protective activity of vitamin D3 alone was higher than that of turmeric root powder or the combined treatment suggests that combinations of these supplements may not always be more beneficial than each agent applied separately.